Impact of lung-function measures on cardiovascular disease events in older adults with metabolic syndrome and diabetes. - Lee, Hwa Mu; Zhao, Yanglu; Liu, Michael A; Yanez, David; Carnethon, Mercedes; Graham Barr, R; Wong, Nathan D (Clin Cardiol, 2018)
BACKGROUND: Individuals with metabolic syndrome (MetS) and diabetes (DM) are more likely to have decreased lung function and are at greater risk of cardiovascular disease (CVD). HYPOTHESIS: Lung-function measures can predict CVD events in older persons with MetS, DM, and neither condition. METHODS: We followed 4114 participants age ≥ 65 years with and without MetS or DM in the Cardiovascular Health Study. Cox regression examined the association of forced vital capacity (FVC) and 1-second forced expiratory volume (FEV ; percent of predicted values) with incident coronary heart disease and CVD events over 12.9 years. RESULTS: DM was present in 537 (13.1%) and MetS in 1277 (31.0%) participants. Comparing fourth vs first quartiles for FVC, risk of CVD events was 16% (HR: 0.84, 95% CI: 0.59-1.18), 23% (HR: 0.77, 95% CI: 0.60-0.99), and 30% (HR: 0.70, 95% CI: 0.58-0.84) lower in DM, MetS, and neither disease groups, respectively. For FEV , CVD risk was lower by 2% (HR: 0.98, 95% CI: 0.70-1.37), 26% (HR: 0.74, 95% CI: 0.59-0.93), and 31% (HR: 0.69, 95% CI: 0.57-0.82) in DM. Findings were strongest for predicting congestive heart failure (CHF) in all disease groups. C-statistics increased significantly with addition of FEV or FVC over risk factors for CVD and CHF among those with neither MetS nor DM. CONCLUSIONS: FEV and FVC are inversely related to CVD in older adults with and without MetS, but not DM (except for CHF); however, their value in incremental risk prediction beyond standard risk factors is limited mainly to metabolically healthier persons.